HISTOPATHOLOGICAL OF STRIPED CATFISH (Pangasianodon hypophthalmus) REARED IN DIFFERENT SALINITIES - Riswan, M; Syawal, Henni; Tang, Usman M; Effendi, Irwan; Kurniawan, Ronal; Wahyuni, Sri; Putri, Mega Novia (Asian Journal of Aquatic Sciences, 2025)
This study aimed to discover the effects of different salinities on histopathological Pangasianodon hypophthalmus. The method used is experimental by applying a completely randomized design (CRD) with four treatments: salinity 0 ppt, salinity 5 ppt, salinity 7 ppt, and salinity 9 ppt. The fish specimen is 8-10 cm in length and weighs 5 g. It was raised in a 54 L tank containing 40 L of water at a density of 2 fish 1 L-1 and kept for 45 days. Feed with commercial pellet 3 times a day in satiation. The results showed histopathological changes in gills and kidneys occurred at a salinity of 9 ppt. Chloride cell hypertrophy and secondary lamella bend in the gill organs, while the kidneys have acute tubular necrosis. Meanwhile, a salinity of 7 ppt resulted in abnormalities in the kidney organs with hemorrhage. It can be concluded that a salinity of 5 ppt indicates a safe salinity condition for the maintenance of striped catfish.